LDLA14: a 14 Gbps optical transceiver ASIC in 55 nm for NICA multi purpose detector project. (1st January 2022) - Chen, Q.; Guo, D.; Zhao, C.; Arteche, R.; Ceballos, C.; Fang, N.; Gan, Y.; Guo, Z.; Murin, Y.; Sun, X.; Yi, L.; ,
Abstract: This paper presents the design and test results of a 14 Gbps optical transceiver ASIC (LDLA14) fabricated in a 55 nm CMOS technology for NICA Multi Purpose Detector (MPD) project. The LDLA14 is a single-channel bidirectional (1Tx + 1Rx) optical transceiver ASIC, including a Laser Driver (LD) module and a Limiting Amplifier (LA) module. It would drive the Vertical Cavity Surface Emitting Laser (VCSEL) of Transmitter Optical Sub-Assembly (TOSA) and receive signals from Photo Diode (PD) of Receiver Optical Sub-Assembly (ROSA), respectively. In the LDLA14, a novel structure of capacitive coupling pre-emphasis is proposed in the output driver of LD to obtain peaking effect without sacrifice the modulation current swing. A shared inductor technology and a Continuous Time Linear Equalizer (CTLE) pre-emphasis structure are added in the output buffer of LA to improve the quality of the output eye diagram. The dimension of LDLA14 is 1.5 mm × 1.3 mm, and the power consumption is 178 mW. The Peak-to-Peak Jitter (PPJ) and Root-Mean-Square Jitter (RMSJ) of the 14 Gbps optical eye diagram of LD in the Tx direction are 22.5 ps and 3.5 ps, respectively. The PPJ and RMSJ of the 14 Gbps electrical eye diagram of LA in the Rx direction are 23.1 ps and 4.7 ps, respectively. The BER tests have been conducted in Tx, Rx directions and the Tx-Rx loop condition, and the BER less than 10 −12 is achieved in all tests.